How science, medicine and engineering has changed how athletes train and perform - Drawer, S.; Cook, C. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Arguably sport science is in its infancy, with the first robust publications truly directed at the subject appearing many years after physiological and medical related treatises relevant to similar subject areas. While understanding in biomedical sciences has progressed almost exponentially since the advent of modern biology of the Watson and Crick era, the same can`t really be said for sport science at its application edge. Often sport science appears undertaken with little reference to more progressive and better work in fundamental fields of biomedical endeavor. This does not necessarily need to be the case. Much work of high caliber in biomedicine and engineering can be piggy-backed on to do innovative work at the applied end of sport science. While innovation is not always viewed as novel or pure in the academic sport science perspective it can both escalate and accelerate applied adoption of good fundamental concepts and indeed correct poorly used and extrapolated ones. A good example of the latter is the understanding (and application) of the hormone testosterone. The clear results in muscle hypertrophy from supraphysiological abuse led to the sport science concept that small changes in natural levels would be equally important, probably an erroneous notion of what testosterone does. Excellent work at the biomedical level has challenged this and as a consequence in turn driven elite athlete applied work demonstrating other important sporting applicable roles of natural testosterone more in keeping also with a biological evolutionary perspective. Similarly an examination of a wealth of biomedical data compared to new descriptive data collected in elite athletes suggest that elites function quite differently to the often used student population sport science study.